PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN KEPEMILIKAN MANAJERIAL TERHADAP RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Sektor Pertanian di BEI) - Ellidianti, Rossy Novia; Murhaban, Murhaban; Zulfa, Andria (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to examine the effect of profitability, capital structure and managerial ownership on stock return with firm value as a moderator veriable in Agricultural Companies in Indonesia Stock Exchange during the period 2009-2018. The number of samples in this study are 10 agricultural companies in the Indonesia Stock Exchange obtained by using purposive sampling technique. Data analysis method used is Panel Data Regression. The results of this study prove that capital structure has negative effect on stock returns, firm value has positive effect on stock returns, profitability and managerial ownership have no significant effect on stock returns. Meanwhile, the moderating effect test prove that firm value is able to moderate the effect of profitability on stock returns, but is unable to moderate the effect of capital structure and managerial ownership on stock returns